VD_FINDINFO HC / 2025 / 259 vom 6. Mai 2025 - VD Tribunal cantonal (2025)
REJET DE LA DEMANDE, MOTIVATION DE LA DEMANDE, INTERPRÉTATIONSENS GÉNÉRAL, FORME ÉCRITE, CRÉDIT-BAILLEUR, LEASING | 1 CO, 12 CO, 16 CO, 18 CO, 311 al. 1 CPC (CH)